TOXICITY OF UREA FERTILIZER TO FINGERLINGS OF Clarias gariepinus AND ASSOCIATED BEHAVIOURAL CHANGES - ADAKOLE, J.A.; LAWAN, S. (Nigerian Journal of Fisheries, 2011)
Clarias gariepinus fingerlings (mean TL, 3.20 ± 1.80 cm; mean weight 1.30 ± 0.50 g) were exposed in a daily renewal bioassay to different concentrations of urea fertilizer (0.00, 25.0, 26.0, 27.0, 28.0, 29.0 and 30.0 g/L), for 96 h to assess its toxicity and behavioural response. The opercular beat, tail fin beat frequencies and mortality were monitored during the exposure period. The pattern of response of opercular beat and tail fin beat frequencies at the various concentrations of the fertilizer generally increased with duration, peaking at the 24th hour after which it began to decline. Other observed behavioural reactions of the exposed fish before mortality were uncoordinated swimming, restlessness, frequent attempts at jumping out of the tank and quietness. Mortality of exposed fish in all toxicant concentrations increased with concentration and duration of exposure. 96-h LC50 of the toxicant was 26.54 g/L with 25.99 g/L and 27.00 g/L as the lower and upper limits respectively. Urea fertilizer caused acute behavioural changes and mortality of C. gariepinus fingerlings.